Music Creation Concerto Polyrhythm – Euphony | Karya musik Concerto Polyrhythm – Euphony - Agung Indrawan Indrawan Wijaksana; I Ketut Garwa (GHURNITA: Jurnal Seni Karawitan, 2024)
Creation of new musical works using important string instruments in Karangasem Regency, Bali. Development and updating of important musical instruments in Karangasem. Adopting kotekan for playing important musical instruments and ggambangan for western music playing techniques, namely polyrhythms. Development of string music is important, by enriching the types of strings on the musical instrument. It is important as a medium that Balinese musical instruments are now being developed to be more modern, with updated musical elements, as well as other contemporary playing techniques. Contains ideas about a western music playing technique, namely polyrhythms, and is packaged nicely with a series of melodies that are pleasant to hear, namely euphony. The combination of these two elements can be combined into a musical work. There are three elements of the method used to realize this work, namely the exploration stage, the design stage and the realization stage. By using experimental music genres, as the foundation for the creation of this new musical work.